A simple multistep etched termination technique for 4H-SiC GTO thyristors. (January 2019) - Li, Zhiqiang; Zhou, Kun; Zhang, Lin; Xu, Xingliang; Li, Lianghui; Li, Juntao; Dai, Gang
Highlights: The SME-JTE can form over ten JTE steps only requiring a few of etching steps. Termination efficiency over 95% with broad etching process window is simulated. High breakdown voltage of 7500 V with efficiency of 91% has been experimentally demonstrated. The SME-JTE is very applicable for high-voltage power devices. Abstract: An edge termination technique, referred to as simple multistep etched junction termination extension (SME-JTE), is presented for 4H-silicon carbide gate turn-off thyristors (4H-SiC GTO). The proposed termination technique can form over ten steps in the termination region with only requiring a few of etching steps. Numerical simulations show that a high termination efficiency over 95% with broad process window for etching depth is obtained for the SME-JTE technique. In addition, a high breakdown voltage of 7500 V has been experimentally demonstrated for the 4H-SiC GTO with 8-step JTE, and which is about 91% of the ideal breakdown voltage for the 50 μm drift layer. The high termination efficiency and simple process of SME-JTE makes it applicable for fabrication of various high-voltage power devices.